2013
DOI: 10.1038/bmt.2013.136
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of invasive fungal infection in pediatric allogeneic hematopoietic SCT recipients

Abstract: This study was aimed at finding predictors of invasive fungal infection (IFI) after pediatric allogeneic hematopoietic SCT (HSCT). All children who received allogeneic HSCT in the Wilhelmina Children's Hospital Utrecht between 2004 and 2012 were included. HSCT data were prospectively collected. Patients were retrospectively classified into high-or low-risk groups for developing IFI using criteria based on available literature. Predictors for the occurrence of IFI were analyzed using Cox regression models. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 26 publications
(47 reference statements)
7
37
0
2
Order By: Relevance
“…We may hypothesize that effective prophylaxis could be valuable also for this subset of patients. 24 Concerning the univariate analysis of prognostic factors, our findings were consistent with other studies showing that corticosteroid dosage, aGVHD, cGVHD and CMV infection could increase the risk of post-engraftment or late IFD. 1,5 In addition, we found that post-engraftment IFD was associated with several risk factors that have been previously related with early or overall IFD, such as older age, delayed neutrophil engraftment, previous SCT, HLA mismatch and non PBSCT.…”
Section: Site Of Infectionsupporting
confidence: 91%
“…We may hypothesize that effective prophylaxis could be valuable also for this subset of patients. 24 Concerning the univariate analysis of prognostic factors, our findings were consistent with other studies showing that corticosteroid dosage, aGVHD, cGVHD and CMV infection could increase the risk of post-engraftment or late IFD. 1,5 In addition, we found that post-engraftment IFD was associated with several risk factors that have been previously related with early or overall IFD, such as older age, delayed neutrophil engraftment, previous SCT, HLA mismatch and non PBSCT.…”
Section: Site Of Infectionsupporting
confidence: 91%
“…Incidence of FI after HCT in analyzed patients was 8.2%, which is in line with presented studies, where it ranged from 8% to 25% . According to Dvorak et al analysis, the incidence of proven or probable FI in pediatric patients during the first year after allogeneic HCT was 13%, which was comparable to the rate reported in adult patients …”
Section: Discussionsupporting
confidence: 86%
“…However, most of the fungal infections in our study were due to Candida spp., which is a contrast to many reports from high‐income countries where Aspergillus spp. may be more prevalent . This difference in distribution may be the consequence of difficulties in the diagnosis of mold infections in low‐ and middle‐income countries due to the low sensitivity of available tests and specific resources, although we did implement routine galactomannan testing and attempted to biopsy suspicious lesions whenever feasible .…”
Section: Discussionmentioning
confidence: 99%